Learn to optimize—a brief overview - Tang, Ke; Yao, Xin (National science review, 2024)
Most optimization problems of practical significance are typically solved by highly configurable parameterized algorithms. To achieve the best performance on a problem instance, a trial-and-error configuration process is required, which is very costly and even prohibitive for problems that are already computationally intensive, e.g. optimization problems associated with machine learning tasks. In the past decades, many studies have been conducted to accelerate the tedious configuration process by learning from a set of training instances. This article refers to these studies as learn to optimize and reviews the progress achieved. The article presents an overview on “Learn to Optimiz”, a paradigm that leverage on a set of training instances to accelerate the tedious configuration process of optimization algorithms.